17β-estradiol promotes recovery after myocardial infarction by enhancing homing and angiogenic capacity of bone marrow-derived endothelial progenitor cells through ERα-SDF-1/CXCR4 crosstalking. (29th October 2018) - Yuan, Zhize; Kang, Lei; Wang, Zhe; Chen, Anqing; Zhao, Qiang; Li, Haiqing
Abstract: 17β-estradiol (E2) has been shown to mediate endothelial progenitor cells (EPCs) to repair infarcted myocardium. Both estrogen receptor α (ERα) and stromal derived factor-1 (SDF-1)/CXCR4 signaling pathways may play a critical role in regulating homing and angiogenesis of EPCs in this process. However, the interaction between ERα and SDF-1/CXCR4 signaling pathways remains unclear. In response to E2, the expression of SDF-1 and CXCR4 in EPCs from ovariectomized BALB/C mice was obviously up-regulated, in addition, the migration and tube formation of EPCs in vitro were also significantly enhanced. However, ERα antagonist (MMP) and CXCR4 inhibitor (AMD3100) significantly decreased the migration and tube length of EPCs, even if mediated by E2. The combined treatment of MMP and AMD3100 exerted more inhibitory effects on migration and tube formation of EPCs induced by E2. In in vivo studies, ovariectomized mice were induced acute myocardial infarction (AMI), and divided into four groups ( n = 6): non-preconditioned EPCs (3 × 10 6 ) group, E2-preconditioned EPCs group, MMP + AMD3100 preconditioned EPCs group, and EPCs pretreated with E2 + MMP + AMD3100 group. E2 group displayed a greater number of homing EPCs, increased capillary density in infarcted myocardium, decreased left ventricular (LV) fibrosis. Nevertheless, these effects of E2 were almost completely blocked by the combined treatment of MMP and AMD3100. E2 can produce cardiovascular protective effects in AMI setting by enhancing homing and angiogenic capacity of EPCs through ERα and CXCR4 signaling pathways, which means that ERα and CXCR4 pathways are effective targets for the development of treatment strategies for AMI.